Dielectric properties of Rhodamine-B and metal doped hydrogels - Okutan, M.; Coskun, R.; Ozturk, M.; Yalcin, O. (ELSEVIER, 2015)
The electric and dielectric properties of Rhodamine-B (RB) and metal ions (Ag+, Co2+, Cr3+, Mn2+ and Ni2+) doped hydrogels have been analyzed in an extended frequency range by impedance spectroscopy. The RB doped hydrogels has been found to be sensitive to ionic conduction and electrode polarization according to the metal doped hydrogels. We have shown that the ionic conductive of RB doped hydrogels is originated from the free ions motion within the doped hydrogels at high frequency. We have also Laken into account the Cl- and N+ ions in the structure of RB provide additional ionic contribution to RB doped hydrogels. (C) 2014 Elsevier By. All rights reserved.
Keywords: Hydrogels; Chemical synthesis; Electrical conductivity; EPOXY-RESIN; ELECTROCHEMICAL PROPERTIES; ELECTRICAL-CONDUCTIVITY; GLASS-TRANSITION; RELAXATION; WATER; SPECTROSCOPY; COMPOSITES; NANOCOMPOSITE; DIFFUSION; Physics